Effects of phase-specific GnRH administration on ovarian functional markers, ovulation timing, and fertility in estrous-synchronized ewes - Cox, Jose Francisco; Navarrete, Felipe; Bocic, Antonio; Saravia, Fernando; Dorado, Jesús (Frontiers in Veterinary Science, 2025)
Suboptimal fecundity rates remain a major limitation of estrous synchronization (ES) protocols in sheep. This study tested the hypothesis that GnRH administration, either to promote follicular diameter homogeneity or to control ovulation timing, could improve ovarian functional outcomes to increase fecundity rates in treated ewes. Experiment 1 assessed whether GnRH administration 36 h after CIDR removal could control the timing of ovulation in ewes treated with a short-term CIDR + PGF₂α protocol, with or without eCG. Ewes were assigned to: CIDR + eCG (Group 1, n = 23), CIDR + eCG + GnRH (Group 2, n = 26), or CIDR + GnRH (Group 3, n = 24). Experiment 2 evaluated the fertility impact of the same protocols across two commercial farms (n = 370), using similar groupings (CIDR, CIDR + eCG, CIDR + eCG + GnRH). All ewes were naturally mated after CIDR removal. Morphological and endocrine markers were recorded to assess follicular growth, ovulation, and corpus luteum (CL) development, while fertility outcomes included pregnancy, lambing, and fecundity rates. Experiment 3 assessed whether GnRH administration during the early follicular phase (day 3) of a Synchrovine protocol could reduce follicular diameter heterogeneity at ovulation. Ewes (n = 45) received either PGF + PGF (controls, n = 23) or PGF + GnRH + PGF (n = 22) and were mated on day 7. GnRH shortened the interval to ovulation (p < 0.0001) and concentrated ovulatory timing (p = 0.0026) in Exp. 1. In Exp. 2, GnRH increased fecundity compared to CIDR + eCG (p = 0.007) and CIDR-only groups (p = 0.004). In Exp. 3, GnRH reduced heterogeneity in follicular diameters (p = 0.004) but did not affect ovulation or fertility (p > 0.10). These findings indicate that GnRH, when administered in the late follicular phase, improves ovulation synchrony and fertility, whereas its earlier use for follicular homogenization alters morphology but not reproductive outcomes.